Cassava starch separation: evaluation of sedmientation by gravity in channels (2014)
The production of cassava starch in Colombia comes mainly from the northern region of the Cauca Department in small agricultural industries known as "rallanderías", in which the settling of the slurry occurs in channels. Due to the fact that the settling process determines the capacity of the starch industry, it is important to evaluate the sedimentation process performed in rectangular channels (0.3 m high; 0.4 m wide; 165 m long), which are generally used in the region. Two main components were evaluated: determination of the change in the concentration of the slurry entering the settling zone and determination of the particle size distribution in the settling zone. In relation to the affluent of the channels, it was found that the concentration of the slurry during strainer operation was between 0.1 to 6% most of the time; the settling of discrete particles, for which the Stokes Law may be applied, predominated. During the settling process, the flow varied between 0.82 to 1.44 L/s with a predominance of laminar flow and a hydraulic retention time greater than 150 minutes. In the first 104m of the channel, particles greater than 10 µm in size were efficiently retained; particles between 6,7 to 8,8 µm were not retained and were discharged into local bodies of water, generating environmental problems.